Exploring the Dimensions of Business Performance: A Conceptual Framework for Sustainable Success - Islam , Md Ariful (South Asian Journal of Social Sciences and Humanities, 2024)
In today’s volatile and cutthroat business environment, companies must overcome a myriad of economic, financial, and social challenges in order to provide consumers with exceptional value. A company’s ability to sustain service quality and the elements that contribute to its improvement is crucial, since businesses in this sector face higher levels of vulnerability and competition than other sectors. Looking at things from several aspects, this research shows how company performance and associated issues are viewed from a broad perspective, which has real-world consequences for everyone involved. The researchers drew on previous research that had already shown how many creative techniques and aspects affected company success. Both academics and practitioners can benefit from the study’s recommendations and suggestions.